The perceptions of consumers aged 18-30 of “lesbian” appeals in advertising (Communicare: Journal for Communication Studies in Africa, 2022)
In an over-saturated market, advertisements have become more risqué as companies viefor consumer attention and lesbian content in advertising seems to be on the increasein mainstream media. This article attempts to discover whether lesbian content inadvertising elicits positive or negative consumer attitudes towards the advertisementand the brand, and to link these attitudes with the intention to purchase the product.By doing so, marketers will be able to ascertain whether this type of advertising appealis effective or whether it offends consumers and therefore decreases product sales.The study was quantitative in nature and used descriptive research in a field setting. Itwas found that there is a significant correlation between tolerance of homosexuality andacceptance of lesbian content in advertising. In addition, these advertisements attractedattention and interest and were not perceived as particularly immoral, exploitive oroffensive by most of the sample population. In terms of attracting attention and interest,and being memorable to consumers, advertisements containing clear lesbian interactionare more effective than those with lower levels of homoerotic t